Community social capital on the timing of sexual debut and teen birth in Nicaragua: a multilevel approach - Bomar Mendez Rojas; Idrissa Beogo; Patrick Opiyo Owili; Oluwafunmilade Adesanya; Chuan-Yu Chen (BMC, 2016)
Abstract Background Community attributes have been gradually recognized as critical determinants shaping sexual behaviors in young population; nevertheless, most of the published studies were conducted in high income countries. The study aims to examine the association between community social capital with the time to sexual onset and to first birth in Central America. Methods Building upon the 2011/12 Demographic and Health Survey conducted in Nicaragua, we identified a sample of 2766 community-dwelling female adolescents aged 15 to 19 years. Multilevel survival analyses were performed to estimate the risks linked with three domains of community social capital (i.e., norms, resource and social network). Results Higher prevalence of female sexual debut (norms) and higher proportion of secondary school or higher education (resource) in the community are associated with an earlier age of sexual debut by 47 % (p < 0.05) and 16 %, respectively (p < 0.001). Living in a community with a high proportion of females having a child increases the hazard of teen birth (p < 0.001) and resource is negatively associated with teen childbearing (p < 0.05). Residential stability and community religious composition (social network) were not linked with teen-onset sex and birth. Conclusions The norm and resource aspects of social capital appeared differentially associated with adolescent sexual and reproductive behaviors. Interventions aiming to tackle unfavorable sexual and reproductive outcomes in young people should be devised and implemented with integration of social process.